Long-term outcomes of bipolar transurethral enucleation and resection of the prostate on patients with benign prostatic obstruction: a 10-year follow-up - Chen, Peijie; Xu, Peng; Liu, Chunxiao (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
OBJECTIVE: We aimed to explore the long-term outcomes of bipolar transurethral enucleation and resection of the prostate (B-TUERP) in patients with benign prostatic hyperplasia (BPH). METHODS: A total of 1195 patients with BPH who underwent B-TUERP from July 2006 to June 2010 were enrolled in this retrospective study. Preoperative data, particularly urodynamic study (UDS) parameters, were collected by questionnaire and examination. Postoperative follow-up was performed at 3, 6, 12, 36, 60 and 120 months, respectively. Demographic, perioperative and functional data were analysed. International Prostate Symptom Score, quality of life and overactive bladder syndrome score (OABSS) were used to assess the functional scores. Predictors of postoperative urgency incontinence were identified by univariate analysis. RESULTS: Long-term outcomes of functional score were significantly better than the preoperative values. All UDS variables, including maximum urinary flow rate, postvoid residual urine volume, compliance, maximum cystometric capacity (MCC), bladder outlet obstruction index, prostatic urethral pressure and detrusor pressure at maximum urinary flow rate, were all significantly improved. No one required reoperation due to recurrent BPH. The postoperative rate of transient urinary incontinence was 31.7%, while the long-term incontinence rate was 0%. Retrograde ejaculation occurred in 44.3% patients who remained sexually active after operation. Patients who had transient urge incontinence were older with preoperative higher OABSS, prostate-specific antigen (PSA) and detrusor overactivity rate and lower MCC. CONCLUSION: B-TUERP is a safe, successful and highly effective treatment for BPH at 10-year follow-up. Increased age, OABSS, PSA level and detrusor overactivity rate are potential predictors for urge incontinence after B-TUERP.
Keywords: následné studie; Prostatic Hyperplasia; lidé; resection; výsledek terapie; prostata; benign prostatic hyperplasia; prostatický specifický antigen; hyperplazie prostaty; bipolar; retrospektivní studie; Quality of Life; outcome; Humans; Urinary Incontinence, Urge; Follow-Up Studies; urgentní inkontinence; mužské pohlaví; Prostate-Specific Antigen; Treatment Outcome; kvalita života; Male; enucleation; Prostate; Retrospective Studies